Concepts, Controversies And Conundrums Of "Alienation:" Lessons Learned In A Decade And Reflections On Challenges Ahead. (28th April 2020) - Fidler, Barbara Jo; Bala, Nicholas
Abstract : There have been significant advances in understandings and practice related parent–child contact problems (PCCPs), with a growing consensus about some issues and continuing controversy about others. It is widely acknowledged that PCCP cases are most fruitfully understood from a multi‐factorial perspective. While some cases may be totally the "fault" of one parent (a parent perpetrating violence or abuse, or a parent exhibiting alienating behavior), in many situations both parents bear some responsibility: focusing on a single cause is rarely helpful. Most professionals and researchers agree that the challenge in practice is to distinguish between false positives and false negatives for both alienation (or unjustified rejection) and realistic estrangement (justified rejection). There is continuing controversy over whether the concept of "alienation" should be used, especially in court proceedings, and a related disagreement about the extent to which family courts are now failing to respond adequately to cases of intimate partner violence (IPV) or child abuse when alienation is also raised. Continuing education, intentional exploration of alternative hypotheses, and active perspective‐taking will contribute to effective professional involvement. Increased parent education and prevention can play an important role, although for the more severe PCCP cases the family courts system will continue to play a critical role. While more research must be done, given the complexity of issues, conclusive findings are unlikely in the near future. Legislators and family justice professionals must make decisions based on a thorough analysis of each family's circumstances in the context of our present knowledge, taking account of the limits of the law. They will often face the conundrum of making decisions in the face of uncertainty. Key Points for the Family Court Community: There have been significant advances in understandings and practice related to parent‐child contact problems (PCCPs), with a growing consensus about some issues and continuing controversy about others. It is widely acknowledged that PCCPs cases are best understood and addressed by relying on a multi‐factorial perspective, a family‐systems approach and coordinated professional services. Attention to false positives and false negatives for both alienation (unjustified rejection) and for realistic estrangement (justified rejection) is necessary. For either of these types of contact problems and for cases involving elements of both, it may be in the child's best interest to remedy the strained parent‐child relationship and for the child to maintain contact with both parents. Legal and mental health professionals involved in decision making, forensic and clinical assessments, and psycho‐educational and clinical interventions face challenges in fact finding and correcting for ubiquitous cognitive biases. Continuing education, intentional exploration of alternative hypotheses, and active dialogue with openness to different perspectives will contribute to effective professional involvement and positive outcomes for families. Increased parent education and prevention can play an important role, although for the more severe PCCP cases the family court system will continue to play a critical role in early intervention, case management, decision making and monitoring some cases post judgment. More research on screening and assessment tools and to differentiate different types of PCCPs and on appropriate interventions is needed. Given the complexity of PCCPs, conclusive research findings are unlikely. Family justice professionals must make decisions and tailor interventions based on an analysis of each family's circumstances using our present knowledge, while recognizing the limits of legal interventions and resource constraints. Often, families and professionals will face the conundrum of making decisions in the face of uncertainty.